2016
DOI: 10.1007/s40641-016-0051-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Arctic Cloud and Climate Research

Abstract: While the representation of clouds in climate models has become more sophisticated over the last 30+ years, the vertical and seasonal fingerprints of Arctic greenhouse warming have not changed. Are the models right? Observations in recent decades show the same fingerprints: surface amplified warming especially in late fall and winter. Recent observations show no summer cloud response to Arctic sea ice loss but increased cloud cover and a deepening atmospheric boundary layer in fall. Taken together, clouds appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(137 citation statements)
references
References 71 publications
6
131
0
Order By: Relevance
“…Overall, CESM can capture general Arctic cloud, radiation, and sea ice features (Barton et al, 2012;Kay et al, 2012;Hurrell et al, 2013). When compared appropriately using a cloud simulator, the seasonal cycle of simulated CF is in better agreement with observed one (Kay et al, 2012(Kay et al, , 2016. Particularly, Community Atmosphere Model version 5 simulated Arctic CF is biased about twice as much winter cloud as the CALIPSO observations.…”
Section: Data Model and Methodsmentioning
confidence: 76%
“…Overall, CESM can capture general Arctic cloud, radiation, and sea ice features (Barton et al, 2012;Kay et al, 2012;Hurrell et al, 2013). When compared appropriately using a cloud simulator, the seasonal cycle of simulated CF is in better agreement with observed one (Kay et al, 2012(Kay et al, , 2016. Particularly, Community Atmosphere Model version 5 simulated Arctic CF is biased about twice as much winter cloud as the CALIPSO observations.…”
Section: Data Model and Methodsmentioning
confidence: 76%
“…A recent series of papers expressing similar conclusions indicates no summertime cloud response to sea ice loss that would offset, even partially, the sea ice albedo feedback [13,17,221,222]. Conversely, a fall and early-winter cloud response exists where slower sea ice growth (i.e., larger-than-average and longer-lasting areas of open water) contributes to enhanced LH flux, which moistens the lower troposphere [46,223], and results in increased cloud amount, cloud base height, and cloud water content [12,13,17,39,217,222]. Kurita [224] found that local sources are the dominant atmospheric water vapor supply for the formation of Arctic low clouds in late autumn and early winter.…”
Section: Cloudsmentioning
confidence: 75%
“…The advent of new satellite observations promises to transform cloud-climate studies [1], especially in the polar regions [2]. Satellite observations are currently exploited to improve cloud parameterization in climate models [3], to measure cloud occurrence and persistence [4], and to study cloud-surface interactions [5].…”
Section: Introductionmentioning
confidence: 99%
“…The radiation balance in the polar regions is yet to be understood due to the lack of accurate cloud climatology [7][8][9]. This is mostly because of the difficulty in detecting clouds by passive satellite sensors over snow and ice surfaces, where it is difficult to distinguish between the reflectance and temperature of clouds and those of the underlying surface [2,10]. A further difficulty in polar regions is the false identification of clouds due to polar atmospheric temperature inversions, which causes clouds to be even warmer than the underlying snow or ice surface.…”
Section: Introductionmentioning
confidence: 99%